Bone Maturation as a Predictive Factor of Catch-Up Growth During the First Year of Life in Born Small for Gestational Age Infants: A Prospective Study - Pepe, Giorgia; Calafiore, Mariarosa; Valenzise, Mariella; Corica, Domenico; Morabito, Letteria; Pajno, Giovanni Battista; Aversa, Tommaso; Wasniewska, Malgorzata (Frontiers in Endocrinology, 2020)
Background: About 85–90% of children born small for gestational age (SGA) experience a catch-up growth that occurs mostly during the first year of life and results in a full stature recovery by the age of 2. Objective: To investigate the relation between bone maturation (BM) and catch-up growth during the first year of life in SGA infants. Method: Newborns whose weight and/or length was <-2 SD for gestational age were classified as SGA (group A). The study included a group of 32 SGA, 21 of which are full term [37–41 gestation weeks (GW), subgroup A1] and 11 preterm (30–36 GW, subgroup A2). Control group (B) consisted of 19 full-term and adequate-for-gestational-age (AGA) newborns. All the participants were born in the same hospital and period (January–December 2017). Chromosomal disorders, congenital defects, and maternal chronic diseases were criteria of exclusion. The study population underwent longitudinal evaluation of growth parameters and BM at 0, 3, 6, and 12 months. Assessment of BM was performed by an ultrasonographic (US) study of Béclard's nucleus (NB) (<3 mm at birth, meaning intrauterine delay of BM). Results: Significantly higher height velocity (HV) was observed in subgroup A2 vs. A1 (32.4 ± 8.0 vs. 25.6 ± 2.9 cm, p = 0.01); nevertheless, more subjects in subgroup A2 had height <-2 SD at year 1 than had subgroup A1 (27.3 vs. 0%, p = 0.01). Intrauterine delay of BM was more common in group A vs. B (59.4 vs. 21.2%, p = 0.0078) and in subgroup A2 vs. A1 (90.9 vs. 42.9%, p = 0.0086). In group A, HV over the first year of life negatively correlates with NB diameter assessed at birth (r = −0.6, p < 0.001) but positively correlates with NB growth (r = 0.52, p < 0.01). Moreover, SGA babies with intrauterine delay of BM showed higher HV and better height gain at 12 months' evaluation than did SGA with adequate BM (29.75 ± 3.1 vs. 23.8 ± 2.7 cm, p = 0.003). Conclusion: Neonatal BM should be regarded as a predictive factor of SGA height gain during the first year of life. US evaluation of NB is a useful noninvasive technique to identify intrauterine delay of BM, which positively correlates with early postnatal catch-up growth of SGA infants.